Copper in sediment, water and suspended particulate matter of the tidal influenced part of the Elbe River sampled in April 2023 (LP20230402) - Hoppe, Pascal; Ortiz, Victoria; Faust, Svenja; Pröfrock, Daniel (PANGAEA, 2025)
Legacy pollutants (e.g. Cu) are well studied and known to deposit in regions of sedimentation along rivers like the Elbe River located in northern Germany. However, in order to help authorities to maintain rivers as important economic transport routes numerical models are used to forecast possible pollution transportation after dredging or sediment relocation. To improve the precision of such models, valid data related to the pollution partitioning behavior and constant model validation is needed. Sediment, water and suspended particulate matter (SPM) were sampled during a sampling campaign in April 2023 and analyzed within the context of the cooperation project CTM-Elbe of BAW and Hereon. The sediment samples were taken by a box corer, homogenized, freeze-dried and wet-sieved to gain the <63 µm grain size fraction. The <63 µm grain size fraction was acid digested and measured by ICP-MS/MS for their (trace) metal mass fractions. The high-volume water samples were centrifuged with a continuous flow centrifuge (CFC) to separate the SPM from the water phase before the SPM samples were freeze-dried. The obtained SPM samples were treated analogously to the sieved sediment samples. The water samples were taken in metal-free GO-FLO sampling bottles and filtered over <0.45 µm polycarbonate filters in the laboratory before acidification with nitric acid. The filtrates were then measured for their (trace) metal concentrations with ICP-MS/MS coupled online to a seaFAST preconcentration and matrix removal system. This data set provides the Cu mass fractions in the fine grain sediment fraction of the SPM together with dissolved (<0.45 µm) Cu concentrations in the water.